Sidelong thinking. Disobedient geographies and subaltern cultures (Altre Modernità, 2016)
My work here develops along a twofold path. On the one hand, and as a researcher committed to postcolonial issues, I share what many theorists say about the need for a more or less stable framework allowing to approach the issue of empire and post-empire in the light of some relatively stable critical categories. On the other, I also feel the gap between theories and some increasingly complex realities that do need a more direct appraisal of the facts implied in a globalized world in the way this need is voiced by Simon Gikandi in his “Globalization and the Claims of Postcoloniality” (2001). To the purpose of imagining a more effective critical frame, I’m borrowing Kara Walker’s notion of sidelong glance to develop a reflection on theories and their usefulness in terms of the actual approach to issues whose profile and complexity are to be intended as not only in progress, but also undergoing a very quick definition and redefinition through time. Starting from Hall’s statement that  the postcolonial may be intended as “sign of desire or  signifier of danger” (1996) and also exploiting the notions of rhizoma (Deleuze & Guattari 1980), subalternity (Spivak 1988) and “Thinking plural” (Said 1993), I’m approaching a number of written, visual and performative texts, from Conrad’s Heart of Darkness to tightly contemporary artistic experiences, to show how both the postcolonial and the decolonial paradigms eventually prove inadequate to the reading of our present condition in terms of the ability to go beyond the traditional Western attitude to the post-colonies.
Keywords: Conrad; Documentary filmmaking; migration; world literature; visual arts